Combined Corneal Wedge Resection And Corneal Cross-Linking For Pellucid Marginal Degeneration: A First Report - Kymionis G; Voulgari N; Samutelela E; Kontadakis G; Tabibian D (Dove Medical Press, 2019)
George Kymionis, Nafsika Voulgari, Erwin Samutelela, George Kontadakis, David Tabibian Ophthalmology Department, University of Lausanne, Jules Gonin Eye Hospital, Lausanne, SwitzerlandCorrespondence: George Kymionis Hôpital Ophtalmique Jules Gonin, 15 avenue de France, Lausanne 1004 SwitzerlandTel +41793332259Email gkymionis@gmail.comBackground: Advanced pellucid marginal degeneration is a debilitating disease that warrants the use of surgery when the visual acuity is reduced and contact lenses are not tolerated anymore. It is traditionally managed with corneal transplantation, however alternative surgical options exist. Corneal wedge resection allows for good visual rehabilitation without the risks of tissue rejection. However topographical and refractive results are in some instance fluctuating. We present here the use of corneal cross-linking in order to stabilize the parameters on the long term.Case presentation: We present here the case of a 53 years old patient with bilateral advanced pellucid marginal degeneration. As he is now intolerant to contact lenses a surgical option is offered to him. In order to avoid using donated tissue through corneal grafting we decide to perform a sectorial lamellar crescentric wedge excision of the thinner inferior part of the cornea involving the pellucid marginal degeneration and suture it. The first eye shows initial good results however after few months regression is observed. The second eye is then treated with the same surgical technique combined with cornea cross-linking. Long-term follow-up shows stabilization and absence of regression in the second eye up to eight months after the surgery.Conclusion: Combining corneal cross-linking with corneal wedge resection in the case of advanced pellucid marginal degeneration patients could be a good option in order to stabilize topographical and refractive results and reduces the risk of regression.Keywords: cornea, ectasia, pellucid marginal degeneration, cornea cross-linking, wedge resection